Medical support of drivers of commercial transport in Ukraine – reformation is necessary - Mikhaylenko, V. L.; Gvantseladze, K. R.; Sheikh Ali, D. H.; Panov, B. V. (Journal of Education, Health and Sport, 2016)
Mikhaylenko V. L., Gvantseladze K. R., Sheikh Ali D. H., Panov B. V. Medical support of drivers of commercial transport in Ukraine – reformation is necessary. Journal of Education, Health and Sport. 2017;7(1):333-345. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.267183 http://ojs.ukw.edu.pl/index.php/johs/article/view/4221 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. Medical support of drivers of commercial transport in Ukraine – reformation is necessary V. L. Mikhaylenko, K. R. Gvantseladze, D. H. Sheikh Ali, * B. V. Panov Odessa National Medical University * Ukrainian Scientific Research Institute of Medicine of Transport of the Ministry of Health of Ukraine, Odessa Article The article provides substantiation of actions for the formation of the medical prevention system and for the medical support of professional activity of commercial transport drivers on the example of shuttle taxi drivers. Information about the work conditions of the shuttle passenger transport drivers, the results of psycho-physiological and clinical examinations of drivers are presented in the article. The health condition of 200 shuttle taxi drivers and 100 non-commercial transport drivers was examined. The conclusions about the necessity of reformation of the existing system of medical provision of commercial transport drivers in accordance with European standards are made. The necessity of further research in the field of medical support of commercial transport drivers is demonstrated. Keywords: commercial transport, occupational health, working conditions and health of drivers, health monitoring.